2014
DOI: 10.1161/strokeaha.114.005836
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Melastatin Subfamily Member 2 Cation Channel Regulates Detrimental Immune Cell Invasion in Ischemic Stroke

Abstract: Ischemic stroke is the second most common cause of death worldwide. Tissue damage is thought to follow a biphasic course. The initial hypoxic damage is determined by immediate neuronal cell death leading to the formation of the infarct core, whereas secondary infarct growth is considered to be a consequence of systemic and local sterile inflammation. 1 Ischemia in the central nervous system is characterized by oxidative stress and the release of a manifold of stress mediators, among them adenosine diphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 24 publications
2
80
0
Order By: Relevance
“…3a) was almost completely prevented by the necrosis inhibitor IM-54, suggesting necrotic cell death, a mechanism eliciting inflammatory responses. This is consistent with the findings from recent transgenic studies that the TRPM2 channel in microglial cells is engaged in inflammatory pain71 and post-ischemic stroke brain damage75 and AD8089.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3a) was almost completely prevented by the necrosis inhibitor IM-54, suggesting necrotic cell death, a mechanism eliciting inflammatory responses. This is consistent with the findings from recent transgenic studies that the TRPM2 channel in microglial cells is engaged in inflammatory pain71 and post-ischemic stroke brain damage75 and AD8089.…”
Section: Discussionsupporting
confidence: 92%
“…We started with using immunofluorescent confocal microscopy to confirm the TRPM2 expression in microglial cells7172737475. Positive immunostaining was observed in cells labelled with an anti-TRPM2 antibody but not in control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The striatal infarct volume was also significantly reduced in the mice injected with lentivirus expressing TRPM2‐specific shRNA into the striatum 2‐3 weeks before ischaemia . Three independent studies compared MCAO‐R induced brain damage in the WT and TRPM2‐KO mice, and these studies provide independent but consistent evidence to show that ischaemia‐reperfusion brain damage was significantly protected by TRPM2‐KO . Furthermore, one of the studies noted no difference in brain damage between the WT and TRPM2‐KO mice that were subjected to permanent ischaemia without reperfusion .…”
Section: Trpm2 Channel In Ischaemia‐reperfusion Brain Damagementioning
confidence: 87%
“…Clotrimazole impedes TRPM2 activity but has many additional effects including inhibition of cytochrome P450 enzymes 68 , block of intermediate conductance Ca 2+ activated K + channels 69 , L-type voltage gated Ca 2+ channels 70 , ATP-gated K + channels 71 , and TRPM8 72 channels, and activation of TRPV1 and TRPA1 channels 72 . A more convincing study using TRPM2 −/− mice showed reduced infarct after ischemia/reperfusion injury, which was a consequence of reduced neutrophil infiltration 73 . Interestingly, transplantation of wild type bone marrow into TRPM2 −/− mice reversed the protective effect of TRPM2 deletion, possibly due to increased neutrophil infiltration 73 .…”
Section: Redox Regulation Of Trpm2mentioning
confidence: 94%